Assessment of Simultaneous Autotrophic–Heterotrophic Denitrification with High Removal of Nitrogen, Sulfur and Carbon: Optimization Through Response Surface Methodology - Huilinir-Curio, C; Montalvo-Martinez, S (John Wiley and Sons Ltd, 2020)
BACKGROUND: Some liquid industrial wastes are rich in sulfur (S), nitrogen (N) and organic matter, causing eutrophication of lakes and rivers. These wastes also are highly toxic to aquatic organisms and pose serious health problems. Biological N removal is performed by denitrification. Heterotrophic denitrifiers oxidize organic matter to CO2 gas and reduce nitrate (NO3 −) to N2 gas, whereas autotrophic denitrifiers oxidize reduced S compounds by reducing nitrate. Thus, a simultaneous denitrification process will allow for the removal of all these elements. RESULTS: A response surface methodology (RSM) was used to analyze the effects of the ratios heterotrophic:autotrophic bacteria (H:A, 0.2–1.9), the molar Ac−(Acetate):NO3 − (0.2–1.05) and thiosulfate (S2O3 2−):NO3 − (0.15–1.1) on the denitrification process. The highest concentrations of sulfate were obtained with H:A = 0.2; Ac−: NO3 − = 1.05 and S2O3 2−:NO3 − = 0.91. CONCLUSION: High NO3 − (average 95.0 ± 3.3%) removals were obtained in all experiments, the optimal values predicted by the RSM were obtained at H:A = 0.54, Ac−:NO3 − = 1.05 and S2O3 2−:NO3 − = 0.41. When analyzing the removal of Ac−, the recommended optimal operating values were: Ac−:NO3 − = 1.05; H:A = 0.37 and S2O3 2−:NO3 − = 0.8–0.9. © 2019 Society of Chemical Industry. © 2019 Society of Chemical Industry